2022
DOI: 10.1111/cid.13077
|View full text |Cite
|
Sign up to set email alerts
|

Artificial biofilm removal in a peri‐implant mucositis model: Efficacy of air polishing technology as adjunct to ultrasonic debridement alone and impact of the site and the depth of mucosal tunnel—An in vitro study

Abstract: Aim The current in vitro model aims to evaluate the adjunctive effect on artificial biofilm removal determined by the use of a glycine‐powder air‐polishing procedure (GPAP) over the ultrasonic debridement (USD) alone when the removal of artificial biofilm on abutment surface is performed. The procedures were carried out also evaluating the impact of the site (mesial, distal, vestibular, and oral) and three different mucosal tunnel depths (2 mm, 4 mm, and 6 mm). Materials and Methods Single tooth implant replac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…On the other hand, deeper mucosal tunnels may reduce the efficacy of bacterial biofilm removal during home oral care procedures and professional maintenance recalls. 70 A recent case-control study reported that deep mucosal tunnels may delay the resolution of experimental peri-implant mucositis when compared with shallow mucosal tunnels. 71 However, long-term studies conducted on large samples are needed to evaluate the real clinical significance of this aspect in influencing the onset of periimplant pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, deeper mucosal tunnels may reduce the efficacy of bacterial biofilm removal during home oral care procedures and professional maintenance recalls. 70 A recent case-control study reported that deep mucosal tunnels may delay the resolution of experimental peri-implant mucositis when compared with shallow mucosal tunnels. 71 However, long-term studies conducted on large samples are needed to evaluate the real clinical significance of this aspect in influencing the onset of periimplant pathologies.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could have a positive effect, as the presence of bone coronal to the implant platform can be regarded as a form of biological shield preventing unwanted bacterial colonization of the treated implant surface. On the other hand, deeper mucosal tunnels may reduce the efficacy of bacterial biofilm removal during home oral care procedures and professional maintenance recalls 70 . A recent case‐control study reported that deep mucosal tunnels may delay the resolution of experimental peri‐implant mucositis when compared with shallow mucosal tunnels 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, an in vitro experiment demonstrated that peri-implant sulci deeper than 4 mm hinder the accessibility of mechanical and air-polishing devices, limiting the percentage of artificial biofilm removal. 26 Moreover, Chan and co. have clinically outlined the role of a "mucosal tunnel" deeper than 3 mm in terms of response to mechanical periimplant mucositis therapy. Implant with deeper peri-implant mucosal tunnel displayed a delayed and incomplete resolution of clinical inflammation after professional cleaning.…”
Section: Regression Modelsmentioning
confidence: 99%
“…[22][23][24] Preclinical studies shed light upon the significant decontamination efficacy of air polishing devices, demonstrating an enhancement in the extent of surface treatment previously achieved by ultrasonic devices. 25,26 However, available evidence displayed conflictive results about the adjunctive effect of GPAP over professional mechanical treatment alone in terms of resolution/reduction of the inflammatory disease (Peri-implant mucositis). 27,28 Therefore, the null hypothesis in the present study asserts that there are no clinical differences when comparing the effects of glycine-powder air-polishing combined with full-mouth ultrasonic debridement against full-mouth ultrasonic debridement alone in the treatment of peri-implant mucositis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation